Transplacental Transfer of Antiretroviral Drugs and Newborn Birth Weight in HIV-Infected Pregnant Women - Ivanovic, Jelena; Nicastri, Emanuele; Anceschi, Maurizio M.; Ascenzi, Paolo; Signore, Fabrizio; Pisani, Giuseppe; Vallone, Cristina; Mattia, Elisabetta; Notari, Stefania; Tempestilli, Massimo; Pucillo, Leopoldo P.; Narciso, Pasquale (Current HIV Research, 2009)
Although it is well known that antiretroviral drugs (ARVs) across the placenta in different extents, few data are available concerning the impact of the transplacental passage of ARVs on newborn outcome. The aim of this study is to evaluate the transplacental diffusion of ARVs and the clinical assessment of the newborn. Mother and cord lopinavir, nelfinavir, atazanavir and nevirapine plasma levels were determined by high-performance liquid chromatography. Newborn gestational age, weight, and Apgar score were recorded. Cord-to-mother ratio (C:M) was calculated to estimate the placental passage of ARVs. Preterm birth was defined as delivery at <37 weeks of gestation and low birth weight was defined as a birth weight of <2500g. Twenty-six HIV-infected pregnant women were enrolled. Nevirapine presented the highest C:M ratio (0.60 ± 0.19), the C:M ratio of nelfinavir and atazanavir was 0.37 ± 0.38 and 0.20 ± 0.14, respectively. The lopinavir level in the cord was undetectable. The observed prevalence rate of neonatal low birth weight and preterm delivery was 19,2% (n = 5) and 15.4% (n = 4), respectively. A significant linear regression analysis was reported between the C:M ratio and newborn birth weight (p = 0.01). Although the role of highly active antiretroviral therapy (HAART) in preventing mother-to-child transmission is indisputable, these data indicate a pharmacological rationale to the association between birth weight and highly active antiretroviral therapy during pregnancy.
Keywords: low birth weight